PERSISTENT INTERMITTENT EDEMA AFTER FACIAL FILLER WITH HYALURONIC ACID: CASE REPORT - Carvalho Vasconcelos, Paula; Vitorino, Felipe (Health and Society, 2022)
Objective: The study portrays the case of a patient who presented episodes of persistent intermittent edema after facial filling with hyaluronic acid. Method: Information was obtained through medical record analysis, pacient anamnesis, image analysis and literature review. Final considerations: The case reported and publications discussion the importance of patient follow-up after procedures, correct diagnosis of adverse events, as well as the management and solution of cases in the initial periods.